Pulpotomy for carious pulp exposures in permanent teeth: A systematic review and meta-analysis. (May 2019) - Li, Yuanyuan; Sui, Bingdong; Dahl, Christian; Bergeron, Brian; Shipman, Peter; Niu, Lina; Chen, Jihua; Tay, Franklin R.
Abstract: Objectives: The most commonly-accepted strategy for managing irreversible pulpitis, an irreversible condition of dental pulp inflammation, is root canal treatment, which is limited by high costs and complex techniques. High success rates have been reported for the use of pulpotomy in managing pulp exposure resulting from extensive caries. The objective of the present work was to evaluate the effectiveness and cost-effectiveness of pulpotomy and associated medicaments in saving permanent teeth with pulp exposure resulting from extensive caries. Sources: Multiple databases were searched on January 12, 2019, without limitations on the language or year of publication. Study selection: Randomized controlled trials comparing pulpotomy with alternative treatments, or comparing two or more medicaments in pulpotomy for permanent teeth with carious pulp exposure were included. Data: Seventeen studies reported in 21 articles were included. Intention-to-treat analyses on studies comparing pulpotomy and other treatment modalities tended to favor pulpotomy. Meta-analysis was not performed on comparisons of pulpotomy and other treatments because of the limited number of studies. Most evidence on comparisons among different pulpotomy medicaments was found in trials comparing mineral trioxide aggregate (MTA) and calcium hydroxide, with the results of meta-analyses favoring MTA. Data were insufficient to determine the cost-effectiveness of successful modality. Conclusions: Pulpotomy is a prospective substitute for root canal treatment in managing permanent teeth with carious pulp exposures, even in permanent teeth with irreversible pulpitis. Large, well-designed trials comparing pulpotomy with other treatments in terms of cost-effectiveness should be informative. Clinical significance: The success of pulpotomy in managing irreversible pulpitis challenges the rhetoric that irreversible pulpitis can only be managed by root canal treatment. Cost-effectiveness analysis rather than analysis on effectiveness of treatment outcome alone should be considered in all health care domains to evaluate the benefits of alternative treatment options.